The Image of Pensive Christ in the Works of Jędrzej Wowro, Antoni Rząsa and Antoni Toborowicz - Ścisłowska, Hanna (Sensus Historiae, 2022)
Who is a folk artist? What is folk art? According to the definition that I found in “Dictionary of Inspiration” and the description of the classification of professions, folk artist creates original and individual works based on regional folk traditions, with the use of skills received through direct transmission of folk art. On the other hand, folk art stands for artistic creativity of the primary type, arising spontaneously and directly, from beginning to end, from the aesthetic needs of a man who, without being guided by any theories, instinctively reflects what he feels as an individual belonging to his cultural circle. One of extraordinary folk artists was Jędrzej Wowro (Andrzej Wawro), Beskid folk sculptor, religious artist and woodcarver of the interwar period, from the village of Gorzeń Dolny near Wadowice, in the province of Lesser Poland. The main theme of his works were figures of saints and Christ, including the Sorrowful Christ. The next artist and sculptor from the Subcarpathian region is Antoni Rząsa. He was not a typical religious or folk artist, although his works refer to traditional art. The last artist, Antoni Toborowicz, is somewhere in-between. He uses traditional form, but at the same time his sculptures are very modern and imaginative as if from a children’s story. All these sculptors are very unique and characteristic.